2019
DOI: 10.1111/acel.12935
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ supplementation rejuvenates aged gut adult stem cells

Abstract: The tissue decline due to aging is associated with the deterioration of adult stem cell function. Here we show the number and proliferative activity of intestinal stem cells (ISCs) but not Paneth cells decline during aging, as does ISC function assessed ex vivo. Levels of SIRT1 and activity of mTORC1 also decline with aging. The treatment with the NAD(+) precursor nicotinamide riboside (NR) rejuvenates ISCs from aged mice and reverses an impaired ability to repair gut damage. The effect of NR is blocked by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 31 publications
5
96
0
Order By: Relevance
“…Both SIRTs have been shown to regulate inflammation in the gut (Akimova et al, 2014;Lo Sasso et al, 2014;Wellman et al, 2017;Zhang et al, 2018). We found that compared with fetal EDMs, aged EDMs expressed less SIRT1 and 6 ( Fig 3B-Left, Middle), consistent with the previous observations of their decline in the aged gut (Liu et al, 2017a;Igarashi et al, 2019). Because age-associated changes in gut microbiome composition is correlated with increases in the pro-inflammatory marker serum monocyte chemoattractant protein (MCP-1) (Conley et al, 2016), which in turn has been implicated in aging-related macrophage dysfunction (Thevaranjan et al, 2017), we analyzed this cytokine in the aged EDMs.…”
Section: Resultssupporting
confidence: 90%
“…Both SIRTs have been shown to regulate inflammation in the gut (Akimova et al, 2014;Lo Sasso et al, 2014;Wellman et al, 2017;Zhang et al, 2018). We found that compared with fetal EDMs, aged EDMs expressed less SIRT1 and 6 ( Fig 3B-Left, Middle), consistent with the previous observations of their decline in the aged gut (Liu et al, 2017a;Igarashi et al, 2019). Because age-associated changes in gut microbiome composition is correlated with increases in the pro-inflammatory marker serum monocyte chemoattractant protein (MCP-1) (Conley et al, 2016), which in turn has been implicated in aging-related macrophage dysfunction (Thevaranjan et al, 2017), we analyzed this cytokine in the aged EDMs.…”
Section: Resultssupporting
confidence: 90%
“…Treatment with the NAD + precursor nicotinamide riboside reverses this phenotype and can promote repair of gut damage. Strikingly, this effect is found to be blocked by rapamycin or the SIRT1 inhibitor EX527 (185). These findings obviously contrast with some of the others discussed above, and more work is needed to resolve these controversies.…”
Section: Aging In the Mammalian Intestinementioning
confidence: 71%
“…Recent findings have highlighted age-related changes in the mammalian intestine and have begun to address the role stem cells may play in functional decline. [14][15][16][17] Specifically, ISCs from mouse, and potentially human beings, show a decrease in regenerative capacity as a result of decreased Wnt signaling. 16,17 Our data suggest that human SI and colon crypt cells differ with respect to epigenetic age; however, whether this is physiologically relevant, as determined by functional changes with age, remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse SI, aging is associated with decreased crypt repair after irradiation, decreasing ISC numbers, slower contribution of Lgr5þ cells to the intestinal epithelium as determined by in vivo fate-mapping experiments, and decreased organoid-forming capacity in vitro. [13][14][15] In addition, decreased Wnt signaling in aged animals impaired the ability of mouse ISCs to maintain homeostasis and contributed to decreased organoid-forming capacity in vitro. 16,17 By contrast, dietary restriction, a lifespan extending intervention, enhanced stem cell numbers and improved regenerative capacity, whereas short-term fasting enhances organoid formation in aged mice.…”
mentioning
confidence: 99%